Two-year results of carotid artery stenting - Şakir Arslan; Erkan Köklü; İsa Öner Yüksel; Göksel Çağırcı; Nermin Bayar; Akar Yılmaz; Görkem Kuş; Nurgül Yılmaz; Yasemin Biçer Gömceli; Bekir Erol (Türk Kardiyoloji Derneği Arşivi, 2014)
Objectives: The effectiveness of carotid artery stenting (CAS) for primary and secondary prevention of ischemic stroke has been demonstrated. The aim of our study was the clinical and radiological evaluation of the reliability of the CAS procedure over a two-year follow-up period. Study design: This study included 120 patients (mean age, 68 (48-86) years) admitted to our hospital between December 2010 and March 2013 for whom CAS was decided in the neurology, cardiovascular surgery and cardiology council. Symptomatic cases with more than 50% stenosis by angiography and asymptomatic patients with stenosis of more than 70% were included in the study. 80% of the asymptomatic patients were those detected during the screening before the coronary bypass surgery. Results: The success rate of the procedure was found as 97.5%. No mortality or myocardial infarction was observed in any of the patients in whom CAS was applied successfully. In 1 symptomatic patient (0.8%), ischemic cerebrovascular event with sequelae was observed 24 hours after the procedure. In total, transient ischemic attack was observed in 2 patients (1.7%) 6 and 11 months after the procedure. Asymptomatic restenosis was detected in 3 patients (2.5% of the total, with 2 in the asymptomatic and 1 in the symptomatic group). Symptomatic restenosis was not observed. None of the patients experienced hyperperfusion syndrome. Conclusion: We believe the CAS procedure can be performed safely in symptomatic and asymptomatic patients with low complication and high success rates.